Does Social Support Moderate Wound Pain and Health-Related Quality of Life in Patients With Chronic Wounds? A Multicenter Descriptive Cross-sectional Study. Issue 4 (July 2021) - Ren, Hui; Wang, Daguang; Ding, Yanming; Hu, Haiyan; Qin, Zeying; Fu, Xiaojin; Hu, Yueyang; Cao, Ruilin; Liang, Leilei; Li, Chuanen; Mei, Songli
Abstract : PURPOSE: We sought to explore the relationships among social support, health-related quality of life (HRQOL), and wound pain, and to examine whether social support would moderate the relationship between wound pain and HRQOL. DESIGN: A multicenter descriptive cross-sectional study. SUBJECTS AND SETTINGS: Individuals with chronic wounds attending wound clinics affiliated with 3 public hospitals in Beijing, China. METHODS: Sociodemographic and wound characteristics of 162 participants were retrieved from medical records. Participants completed questionnaires for wound-related pain intensity (Numerical Rating Scale), social support (Social Support Rating Scale), and HRQOL (Medical Outcome Study Short Form-36). The moderating effect analysis was examined using the PROCESS analytic tool developed by Hayes, based on the bias-corrected bootstrapping method. RESULTS: Results revealed that higher pain intensity was significantly related to lower HRQOL ( P < .01), and higher social support was associated with better HRQOL ( P < .01). However, there was no significant correlation between social support and wound pain ( P = .55). Importantly, the moderating effect of social support on the relationship between wound pain and HRQOL was statistically significant ( P = .008). CONCLUSIONS: We found that social support moderated the impact of wound pain on HRQOL in patients with chronic wounds. This finding suggests that support obtained from social networks may be a beneficial intervention to improve the HRQOL of patients with chronic wounds, especially those suffering from high-intensity wound pain.